Desain Portofolio Optimal untuk Keputusan Investasi pada Fase Krisis Keuangan - Deddy Saptomo; Insannul Kamil; Elita Amrina; Mego Plamonia (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2017)
This research aims to design optimal portfolio with a case study of stocks listed on the Indonesia Stock Exchange (IDX) that conduct transactions in the period 2011-2015. The sample used were 396 companies listed on nine sectors in BEI. Arbitrage Pricing Theory (APT) method is used to determine the realized return, expected return, and efficient portfolio involving four macroeconomic factors (Stock Price Index (IHSG), interest rate of Indonesian Bank Certificates (SBI), Inflation and Exchange Rate of Rupiah against the US Dollar). Efficient portfolio is formed by 231 undervalued companies. While the optimal portfolio with the Excess Return to Beta (ERB) approach was formed by 42 companies with a ERB value greater than (or equal to) cut-off point (0,1912). Under the uncertainty of the investment climate due to the global financial crisis, the decision to make investments needs to be done carefully and consider various factors, including macroeconomic factors. This research has succeeded in designing an optimal portfolio that can be a guide for investors to determine investment decisions.